The effect of hypoxia on the secretome of human glioblastoma multiforme cells - T. I. Kushnir; N. E. Arnotskaya; I. A. Kudryavtsev; A. A. Mitrofanov; A. K. Bekyashev; V. E. Shevchenko (Успехи молекулярной онкологии)
Background. Glioblastoma multiforme (GBM) develops in the hypoxic microenvironment, which plays an important role in the pathogenesis of the disease and is closely associated with tumor growth, development and poor prognosis. Hypoxia increases the resistance of tumor cells (TC) to radiation therapy and chemotherapy, promotes the appearance of an aggressive TC phenotype, leading to the disease recurrence. The molecular mechanism of hypoxic action on the secretome of GBM cells, which is involved in the formation of the tumor microenvironment, remains unclear. Also, markers of the aggressive hypoxia-associated phenotype of tumor cells have not been established. The purpose of research – to study the molecular mechanisms of the hypoxia-associated effect on the secretome of the U251 GBM cells.Materials and method. High resolution proteomic mass spectrometry, cell technologies.Results. A total of 1432 proteins were identified in the secretomes of two types of GBM cells (control and experiment). After the action of hypoxia, statistically significant changes in the expression of 390 proteins were registered. 11 proteins showed increase in expression over two orders of magnitude. The intracellular signaling pathways which are responsible for the hypoxia-associated effects on the U251 GMB cells have been identified.Conclusions. Hypoxia significantly affected the proteomic composition of the GBM cells secretome. Five overexpressed secretome proteins, S100A6, HEY1, ZIP3, S100A4, ZEB2, have been proposed as potential markers of the hypoxiaassociated phenotype of GBM, for which participation in the pathogenesis of glioblastoma multiforme has been previously showed.